A Socialised Medical Service (London : The Socialist Medical Association, 1933)
1933 1933 1930s 21 pages hospitals that they trust, although they may not know even so much as the name of any one member of the staff. It may, therefore, be in the interest of the patient to have the power to select his own home doctor. As free a choice of doctor is possible under a State Service as under the present. Unless a practitioner is permitted to become over-worked and, therefore, inefficient, it is impossible for him to deal with more than a certain number of patients, and this applies equally whether he is in private practice or a whole time State official. 6. — DOCTORS MUST BE AT THE SERVICE OF THEIR PATIENTS The present medical services appear to be organised, in so far as any organisation exists at all, on the assumption that the supply of doctors is strictly limited, and, therefore, the time and convenience of the doctors are the only things that matter. As there are at present no maintenance scholarships for the medical profession, no parent can make his child a doctor unless he is able and willing to provide for his maintenance until he reaches the age of at least twenty-two or twenty-three. It follows, therefore, that at the present time the medical profession is recruited almost exclusively from a small portion (about a sixth) of the population. By providing maintenance scholarships to enable boys and girls from the secondary schools to obtain a medical qualification the State will be able to increase the number of qualified doctors to any required extent. The doctors of the future State Service will see their patients largely by appointment and the present long waits will be avoided. A qualified doctor must be available at all times in all hospitals. 7. — THE VALUE OF MEDICAL RECORDS While it is admitted that every family should have a Home Doctor to act as guide, philosopher and friend, it must not be forgotten that a doctor's memory may be defective, and that both patients and doctors may change their place of residence. Therefore, it is of the greatest possible importance that a medical record shall be kept of everyone and that every event of medical significance from birth onward shall be entered by the doctor who sees a patient. Medical records should be kept in duplicate in the Health Centre (see later) and passed on when residence is changed. 8.— THE CONDITIONS OF SERVICE MUST BE SATISFACTORY If medicine is a science it must be progressive. The fact that in the past the main discoveries of medical science have been made by the specialist in hospital and not by the general practitioner does not indicate that there exists an essentially different 6 292/847/1/1